The Preferences of Tourists in Choosing Transportation Modes for Traveling in Bandung City - Herienda, Florensia; Adriani, Hanni; Nofiyanti, Fifi; Abduh, Mohammad Syaltut; Maulana, Alifatqul (Institut Pariwisata Trisakti, 2025)
This study aims to identify tourists' preferences in choosing transportation modes during their visit to Bandung City and to analyze the factors influencing their decisions. The method used is a quantitative approach with surveys and interviews. The study sample consists of 200 tourists, with 150 domestic tourists and 50 international tourists. Data were collected using questionnaires and interviews to gather information related to transportation mode choices, speed, comfort, price, and accessibility factors. The results show that the most commonly chosen transportation mode is Angkot (25%), followed by Trans Metro Pasundan (23%). Travel speed, comfort, and accessibility are the main factors influencing transportation mode choices. Furthermore, differences in preferences are observed between domestic tourists, who tend to prefer economical transportation modes like angkot and TMB, and international tourists, who prioritize comfort such as online taxis or Bandros. The study concludes that transportation mode choices are influenced by practical needs such as affordable prices, comfort, and ease of accessibility. Recommendations for destination managers and the government include improving the public transportation infrastructure to be more efficient and environmentally friendly, as well as utilizing technologies like ride-hailing apps to enhance comfort and accessibility for tourists. Keywords: tourists' preferences, transportation modes, speed and comfort, and transportation accessibility